Quand le stagiaire planifie... une question d'équilibre dans ses décisions - Agnès Deprit; Catherine Van Nieuwenhoven
Planning is an activity of the teacher's profession (Coppé, 2007) that can be pre-active, interactive or postactive depending on when it is in relation to class interactions (Tochon, 1989). This article focuses on pre-active planning, which consists in programming (organizing the content to be taught over time) (Durand, 1996) and preparing (piloting didactically in the short term) the learning sequences (Hamel et Viau-Guay, 2017). What the trainees do when planning their internship is a relatively under-researched area (Coppé, 2007) and even more difficult to understand given that it is organized in informal learning spaces (De Vos, Beausaert, De Wilde et Lecot, 2018). In the context of the initial training of primary school teachers in French-speaking Belgium, this research aims to understand the decisions taken by the trainees who prepare their activities on the basis of the principle of viability (Pépin, 1994; Malo, 2005). To this end, seven students in their final year of training were invited to complete a daily logbook and participate in two semi-directive interviews (Merriam, 2009). The qualitative analysis of the data has allowed on the one hand, to identify the indicators activated in the pre-active decisions for each criterion of the viability principle (efficiency, certainty, comfort); on the other hand, to observe that the criterion of certainty seems, when planning, to have a priority weight in the balance of students' choices.